Evaluation of Electronic Health Record Systems - Nøhr, C. (Yearbook of Medical Informatics, 2006)
The objective of this article is to present an overview of the various considerations to be made prior to evaluating electronic health record (EHR) systems.From the methodological literature, a number of themes for decisions are presented and related to the contemporary EHR situation. Special attention is paid to a number of important methodological themes.Definitive checklists for evaluation of EHR systems can not be recommended, but seven key steps are listed to guide the design of evaluation projects.It is concluded that the issues presented are not completely exhausted and the seven key steps might have to include iterative loops because of interdependencies between some of the steps.
Keywords: Evaluation methodology; medical record; health informatics; electronic health record